Genetic Heterogeneity in Colorectal Cancer and its Clinical Implications - Barranha, Rui (2015)
Despite the recent advances in the development of complementary diagnostic exams and modern targeted therapies, colorectal cancer remains a major cause of morbidity and mortality worldwide. In this context, a lot of research has been conducted in the last years to find new markers of poor prognosis. The existence of a complex tumour architecture formed by multiple subclones genetically heterogeneous has been increasingly considered in recent studies as an element of particular importance. This feature seems to influence factors as relevant as the representativeness of tumour biopsies for genetic diagnosis and the efficacy of targeted therapies.There is growing evidence suggesting a relation between genetic heterogeneity and the patients’ prognosis. The widespread use of next-generation sequencing techniques will allow a better understanding of the true degree of genetic heterogeneity in colorectal tumours, its causes and impact on the course of the disease. In this review we intend to analyse the recent findings related to the genetic heterogeneity of colorectal cancer, as well as its major clinical implications.